Analisis Lean Manufacturing Untuk Menurunkan Waste Waiting Pada Proses Assembly di PT. Z - David Arifin; Muhamad Arman Maulana; Feriyansah Feriyansah; MD. Rafiffallah; Tri Ngudi W (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to identify and reduce waiting waste in the assembly process of product X through the application of lean manufacturing principles. The methods employed include value stream mapping, cycle time analysis, and the implementation of 5S. Conducted at PT. Z, the results indicate several significant sources of waiting waste, such as additional movements during material disposal and retrieval, waiting for materials during the buffing process, and machine downtime during the welding bracket process. By applying lean tools such as balanced production, single minute exchange of die, and a kanban system. Furthermore, resource utilization improved, and product quality also showed enhancement. The conclusion of this research emphasizes that lean manufacturing is an effective approach to addressing waiting waste issues in the assembly process and enhancing production efficiency.